Poverty, race and skin color: Perceptions and relationships among children at school - Moreira, Maria de Fátima Salum; Aguiar, Deise Maria Santos de (Revista Eletrônica de Educação, 2015)
<!--[if gte mso 9]> <![endif]--><!--[if gte mso 9]> Normal 0 21 false false false PT-BR X-NONE X-NONE MicrosoftInternetExplorer4 <![endif]--> DOI: http://dx.doi.org/10.14244/198271991475 Here are presented the results of a research whose objective was to analyze what were saying and how were acting poor and/or black boy(s) and girl(s) about unequal treatment, shaped by discrimination through mockery, swearing, derogatory nicknames, separations, among other things, experienced in school. These children were students from the 5th year of primary school, in a public school located in a mid-sized city in the interior of São Paulo, Brazil. It was intended to undertake an analysis of the practices of class and racial differentiation that hierarchize, discriminate and exclude certain children, performed by adults and/or by children themselves. The ethnographic study made use of their stories, a questionnaire about denomination and classification of color/race, answered by children in the classroom, socio-economic survey, observations of children in different school environments and semi-structured interview with children and teacher. Among other results, it was confirmed that, children that were black, black and brown, poor and with a history of educational failure, suffer bigger discrimination at school from teachers and other children. In addition it was found that even among those who are poor and or black, it takes place the building of borders for the distinction that each one makes of themselves in relation to others. Therefore, the research provided the acknowledgement of the diversity of positions related to the recognition that they make regarding their identification of race and class. When verifying how children's actions are mediated by school educational practices, we support that in such spaces it should be granted the conditions of possibilities for them to speak - and be heard - about their doubts and desires, about what they do and why they do it, in the relations between them. Finally, provide the emergence of their curiosities, imagination and inventiveness to, maybe, see the burst of something new in our world that strives for incompleteness. Keywords: Children, Poverty, Race, School. <!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <![endif]--><!--[if gte mso 9]> Normal 0 21 false false false PT-BR X-NONE X-NONE <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <mce:style><! /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Tabela normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-qformat:yes; mso-style-parent:""; mso-padding-alt:0cm 5.4pt 0cm 5.4pt; mso-para-margin:0cm; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-fareast-font-family:"Times New Roman"; mso-fareast-theme-font:minor-fareast; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; mso-bidi-font-family:"Times New Roman"; mso-bidi-theme-font:minor-bidi;} --> <!--[endif] -->